Biogeographic relationships of Pliocene and Pleistocene North-western African Mammals - (:unkn) unknown (My University, 2010)
North-western Africa, today included in the Palaearctic realm, is well separated from the Ethiopian province by the Sahara, but the distribution of large mammals shows that these biogeographic domains cannot simply be extrapolated to the late Cenozoic. In the latest Miocene and earliest Pliocene, there were close connections with central Africa, but also remarkable similarities with East Africa, in some instances reaching the species level. There is no evidence of northern influence among large mammals, although several small mammals had a wide range in the Mediterranean. East African or pan-African forms are also largely predominant in the well sampled Late Pliocene, their low diversity resulting probably from local environmental conditions. There are but a few immigrants from Eurasia, mostly carnivores. During the Early Pleistocene, limited exchanges occur with the Middle East, but many more with the rest of Africa. By the Middle Pleistocene similarities with East Africa reach their climax, and it is only with the latest part of this period that some northern immigrants put a Palaearctic stamp on this fauna, the “Ethiopian” character of which decreases by extinction of many of its elements.
Keywords: African Research